THE INVESTIGATION OF ORGANOPROTECTIVE PROPERTIES OF 2-HYDROXY-N-NAPHTHALENE-1-YL -2-(2-OXY-1,2-DIHYDRO-INDOLE-3-YLIDEN)-ACETAMIDE - Lutsenko, R.V.; Sydorenko, A.H.; Koiro, O.O.; Tsyvunin, V.V.; Larinovska, Yu.B. (World of Medicine and Biology, 2021)
In experiments on 64 white male rats, the effect of 2-hydroxy-n-naphthalene-1-yl-2-(2-oxy-1,2-dihydro-indole-3-yliden)-acetamide (12 mg/kg) compared to ethylmethylhydroxypyridine succinate (50 mg/ml) on the course of acute kidney injury caused by glycerol and tetrachloromethane hepatitis was studied. It has been found that the use of 2-hydroxy-n-naphthalene-1-yl-2-(2-oxy-1,2-dihydro-indole-3-yliden)-acetamide against the background of tetrachloromethane hepatitis exhibits hepatoprotective properties, as evidenced by a decrease in the organ mass coefficient and the activity of enzymes-markers of damage to hepatocytes of alanine aminotransferase and aspartate aminotransferase in blood serum. The hepatoprotective effect of the studied compound is not inferior to ethylmethylhydroxypyridine succinate. In addition, a derivative of 2-oxyindoline-3-glyoxylic acid reduced the onset time of thiopental anesthesia. In acute glycerol-induced kidney injury, 2-hydroxy-n-naphthalene-1-yl-2-(2-oxy-1,2-dihydro-indole-3-yliden)-acetamide had only the antiproteinuric action and did not show sufficient protective effect. This indicates the absence of the nephroprotective effect in the substance and possible side effects from the kidneys.